DIFFERENT CLASSIFICATION OF FAIRYTALE DISCOURSE IN WORLD AND UZBEK FOLKLORE - Yusupova, Omina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
In the article the classification of tales, the stages of studying fairy tales in world and Uzbek folklore are widely discussed. In addition, the article describes the main characteristics of fairy tales and their stages of development. This research considers the field of folklore as the main subject of its study. Further goal of the work is to study fairy tales on a large scale and to make a contribution to folklore studies. In the present article, the author deeply analyzed the classification of fairy tale discourse through examples.